A Hybrid Model of the Akamai Adaptive Streaming Control System - L. De Cicco; Giuseppe Cofano; Saverio Mascolo (IFAC Proceedings Volumes, 2014)
Video streaming is becoming the application generating the largest fraction of the Internet traffic. Adaptive video streaming adds to classic video streaming the feature of dynamically adapting the video bitrate to track the time-varying network available bandwidth, avoid playback interruptions and ensure the delivery of the best video quality. In this paper we focus on the adaptive video streaming control system employed by Akamai, a major CDN operator whose video delivery system is used by several video streaming platforms, including Livestream. Differently from the typical client-side control, Akamai employs an interesting and unique hybrid client/server control architecture. Our purpose is to derive and validate a closed loop mathematical model of the control system, which turns out to be a hybrid automaton. The model is then analyzed to derive key properties which can be used to properly tune the controller parameters.
19th IFAC World Congress